Dative, instrumental and local cases of plural nouns of masculine and middle family in the Ukrainian literary language of the ХVII th century (on the basis of «Synopsis» and «Chronicle» of Ph. Sophonovich) - Фунікова, Тетяна Вікторівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article is based on the historical materials. This investigation is dedicated to the analysis of dative , instrumental and local cases of the noun system in «Synopsis» and «Chronicle» by Ph. Sophonovich, annalistic monuments of the ХVII th century, in the context of the Ukrainian literary language of the ХVII th century. In article both archaic and new forms of noun in chronicle are revealed.The most important phenomenon in the system of the declension of nouns is the destruction of the old system of the declension, organized according to the structure of stems, and setting up a new system, based on the gender principle. It is determined that the language of  «Synopsis» is literary Church Slavonic language in Slavo-Ukrainian variant from which foreign structural components are gradually removed and replaced with  the Ukrainian ones. The analysis of case category gave the possibility to find out that some cases receive two or three parallel case forms caused by new grouping of nouns on gender principle as well as such processes as internal analogy, development of animate and inanimate objects category, number, step-by-step disappearance of dual number. At the same time some cases are multifunctional. In word-changing of nouns of new types of declension of the Ukrainian literary language of the ХVІІ century inflexions of some cases of different declension may be unified. New types of declension gave the possibility to get rid of archaic Church Slavonic forms and use inflexion forms on the new principles. In this work both archaic and new forms of nouns in chronicles which are typical for the modern Ukrainian literary language are revealed. On the basis of the investigation it is concluded that the noun system in the language of «Synopsis» and «Chronicle» by Ph. Sophonovich is a phase of transition from noun system of Old Ukrainian period to noun system of modern Ukrainian literary language. There is established that the noun system in «Synopsis», on the one hand, Keeps many archaic forms, many old inflexions and, on the other hand, includes different new forms (new inflexions, forms of plural number, etc.).